(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim/Purpose: -Type 2 Diabetes Mellitus affecting around major population around the world and with increasing ratio in near future. There is modification in tissue cells which fails to respond to insulin properly.(FGF-23) Fibroblast Growth Factor-23 known as a hormone composed of peptides circulating in blood synthesized by (osteoblast) bone cells. FGF-23 can exhibit physiological functions in conjugation to bone metabolism like bone calcification and hematopoiesis.An important nutrient of osteoblast cells has been a glucose and also many studies have shown significant alteration of bone formation in increased glucose level. Hyperglycemia affects bone remodeling in cells of bones, insulin signalinginteraction and metabolism of bones through insulin receptors directly or indirectly. Hence, this study is designed to estimate levels of FGF-23 in bone metabolism among healthy group, prediabetic and in people suffering from type-2 diabetes mellitus.Methods: -The type of present study is observational and is designed as a case control study performed in hospital. Total of 225volunteers were taken in control group, prediabetes and 75 diabetes mellitus type 2patients. Standard deviation and was analyzed using one-way ANOVA test and for further analysis for specific differences between 3 groups with post-hoc tukey test. Values of P<0.05 was taken as significant.Results: -Our results shows positive relationship for the parameters tested when found between the groups using test known as posthoc tukey (p<0.001).Conclusion: -The present study gives clear insight about bone remodeling and bone formation when controlled by FGF-23 hormone and can be predicted as biological possible bio-marker in the bone metabolism. Henceforth, more advanced studies are required for detailed examination of FGF-23 physiological actions on bone metabolism and its inter-relationship with insulin resistance especially diabetic patients.